Does Polycystic Ovary Syndrome Itself Have Additional Effect on Apelin Levels? - Dilek Benk Silfeler; Cumali Gokce; Raziye Keskin Kurt; Nigar Yilmaz Atilgan; Oktay Hasan Ozturk; Ebru Turhan; Ali Baloglu (Obstetrics and Gynecology International)
Objective. The present study was designed to compare serum levels of apelin between lean PCOS women and healthy women with regular menses. Study Design. A total of 30 lean patients with PCOS and 30 healthy subjects were included in this study. Serum apelin levels were compared between groups. Results. Serum apelin levels in lean PCOS patients were not significantly different from the control subjects. Conclusion. Our findings indicate that PCOS itself does not seem to change apelin levels. Further investigation on a large number of subjects will need to be conducted to prove the consistent or variable association in PCOS.